Advances in Velloziaceae: discovery of four new species of Vellozia Vand. from Central Brazil - Schindler, Bianca; Figueira, Maurício; Simon, Marcelo Fragomeni (Phytotaxa, 2025)
Four new species of Vellozia (Velloziaceae) from the Cerrado of Central Brazil are here described and illustrated: Vellozia aroejariensis, from Chapada dos Guimarães in Mato Grosso, and V. glocimarii, V. nana, and V. veadeirensis, from northern Goiás, Brazil. We provide a detailed morphological description of each species, emphasizing the features that set them apart from closely related species within the genus. These distinctions are further discussed in the diagnosis and comments section. We also provide information on their geographical distribution, habitat, geological context, phenology, and preliminary conservation assessment. Field images offer visual support for the descriptions. All four species are narrow endemics, restricted to specific rocky outcrops habitats. This study contributes to a deeper understanding of Vellozia diversity and emphasizes the critical role of Cerrado rocky outcrops to plant endemism and conservation.